2018
DOI: 10.1371/journal.pone.0206081
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning approach to automatic detection of early glaucoma from visual fields

Abstract: PurposeTo investigate the suitability of multi-scale spatial information in 30o visual fields (VF), computed from a Convolutional Neural Network (CNN) classifier, for early-glaucoma vs. control discrimination.MethodTwo data sets of VFs acquired with the OCTOPUS 101 G1 program and the Humphrey Field Analyzer 24–2 pattern were subdivided into control and early-glaucomatous groups, and converted into a new image using a novel voronoi representation to train a custom-designed CNN so to discriminate between control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…In a total of 345 eyes (156 glaucoma and 189 non-glaucoma), Goldbuam et al reported that the Gaussian (MoG) model, among the machine learning models, yielded the highest performance (AUC: 0.923) in detecting glaucoma on 24-2 humphrey VF. With the advent of deep learning, Kucur et al utilized numerical total deviation plots of 2267 24-2 VF samples (201 subjects) and a customized CNN to train the deep learning system 24 , showing a precision score of 0.874 that is better than other conventional machine learning models. For glaucoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…In a total of 345 eyes (156 glaucoma and 189 non-glaucoma), Goldbuam et al reported that the Gaussian (MoG) model, among the machine learning models, yielded the highest performance (AUC: 0.923) in detecting glaucoma on 24-2 humphrey VF. With the advent of deep learning, Kucur et al utilized numerical total deviation plots of 2267 24-2 VF samples (201 subjects) and a customized CNN to train the deep learning system 24 , showing a precision score of 0.874 that is better than other conventional machine learning models. For glaucoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Kucur et al . 19 developed a convolutional neural network (CNN), a kind of deep-learning architecture, to discriminate early glaucoma from normal glaucoma. They used two visual field examinations as input data, OCTOPUS 101 perimeter and Humphrey visual field 24-1.…”
Section: Discussionmentioning
confidence: 99%
“…CNNs have also been shown to discriminate between controls and early glaucoma on visual fields with a higher accuracy than use of standard perimetry mean deviation (MD) or neural networks without convolutional features. 72 …”
Section: Introductionmentioning
confidence: 99%